Znaczenie edukacji w kształtowaniu poczucia wpływu młodzieży gimnazjalnej = Importance of education in shaping a sense of influence among junior high school students - Turska, Elżbieta; Prokosz, Małgorzata (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Being convinced about the possibility of making changes in your life is very important for a young adolescent entering the world of adulthood. It will let them overcome difficulties and failures. Theoretical reflections concerning the importance of education in shaping a sense of influence among young people are reflected in the results of empirical research presented in the article.
Keywords: młodzież gimnazjalna; szkolnictwo ponadpodstawowe; sprawstwo podmiotowe